2021
DOI: 10.1002/cam4.4030
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and associated factors of sudden unexpected death in advanced cancer patients: A multicenter prospective cohort study

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
(45 reference statements)
0
8
1
Order By: Relevance
“…Our results were different from those reported by two previous studies that explored breathlessness as an associated factor for unexpected death [ 4 , 6 ]. However, our results revealed that patients experiencing shortness of breath were less likely to die unexpectedly.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results were different from those reported by two previous studies that explored breathlessness as an associated factor for unexpected death [ 4 , 6 ]. However, our results revealed that patients experiencing shortness of breath were less likely to die unexpectedly.…”
Section: Discussioncontrasting
confidence: 99%
“…The definition of unexpected death or sudden death among terminally ill patients is another important issue to be discussed. Multiple studies have researched the associated factors surrounding unexpected death [ 4 , 6 ]. Although PCOC is commonly utilized in palliative care services in Australia, Ireland, and Taiwan [ 33 ], few studies have used PCOC data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, four major definitions of sudden unexpected death have been utilized in the palliative care literature: rapid decline death (i.e., a sudden death preceded by functional decline over 1–2 days) [ 46 ], surprise death (i.e., the primary responsible physicians answered “yes” to the question, “Were you surprised by the timing of death?”) [ 9 ], unexpected death (i.e., a death that occurred earlier than the physician had anticipated) [ 9 ], and performance status–defined sudden death (i.e., a death that occurred within 1 week of functional status assessment with an Australia-modified Karnofsky performance status ≥ 50) [ 47 ]. Using these four definitions, Ito et al [ 13 ] prospectively followed 1,896 PCU patients, and found that the incidence of rapid decline death was the highest (30-day cumulative incidence: 16.8%), followed by surprise death (9.6%), unexpected death (9.0%) [ 46 , 48 ], and performance status–defined sudden death (6.4%) [ 13 ]. These findings were generally consistent with the IPOD study, which found that approximately 10% of PCU deaths were unexpected by physicians and nurses based on the “surprise” and “unexpected death” questions [ 9 ].…”
Section: Prognostication Of Impending Deathmentioning
confidence: 99%